OROFACIAL PAIN;PROBLEM BASED LEARNING (SYDNEY UNIVERSITY PRESS, 2005)
This book takes a problem-based learning approach to orofacial pain, focusing on neuropathic trigeminal pain and persistent temporomandibular disorder. Topics covered include symptomology of several types of orofacial pain, pain progression and the psychosocial factors involved in pain.